2014
DOI: 10.1016/j.nuclphysb.2014.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Conformal higher-spin symmetries in twistor string theory

Abstract: It is shown that similarly to massless superparticle, classical global symmetry of the Berkovits twistor string action is infinite-dimensional. We identify its superalgebra, whose finite-dimensional subalgebra contains $psl(4|4,\mathbb R)$ superalgebra. In quantum theory this infinite-dimensional symmetry breaks down to $SL(4|4,\mathbb R)$ one.Comment: 20 pages, LaTeX. v2: section 3 undergone major revision, others - minor improvements including correction of typos. Version accepted to Nuclear Physics

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In Appendix C, we will present the remaining OPEs between them. We observe that the first order poles in the right hand sides of these OPEs (together with the symmetric or antisymmetric combinations of the left hand sides of the OPEs) contain the higher spin generators as well as the new higher spin generators 21 . In general, in these OPEs, there are also fourth, third and second order poles we do not analyze them in this paper explicitly.…”
Section: The Opes Between the Weight-1 Generators And The Weight-3 Ge...mentioning
confidence: 88%
“…In Appendix C, we will present the remaining OPEs between them. We observe that the first order poles in the right hand sides of these OPEs (together with the symmetric or antisymmetric combinations of the left hand sides of the OPEs) contain the higher spin generators as well as the new higher spin generators 21 . In general, in these OPEs, there are also fourth, third and second order poles we do not analyze them in this paper explicitly.…”
Section: The Opes Between the Weight-1 Generators And The Weight-3 Ge...mentioning
confidence: 88%
“…Use of twistor-like variables for a discussion of conformal fields may be found in refs. [68][69][70]. We note also that Lorentz algebra vector oscillators are popular in the framework of BRST approach to higher-spin fields (see, e.g., refs.…”
Section: Jhep02(2023)043mentioning
confidence: 89%
“…In Ref. [17], Berkovits and Witten have shown that conformal gravity appears in the context of string theory on twistor spaces; see also [18][19][20][21][22]. In Ref.…”
Section: Introductionmentioning
confidence: 99%